Returns to Publicly Owned Transport Infrastructure Investment. A Cost Function/Cost Share Approach for Norway, 1971-1991 - Torstein Bye; Alexandra Katz (Statistics Norway, Research Department, 1995)
An issue of major concern to politicians and policy-makers around the world today is whether transport infrastructure investments, such as those in roads and airports, generate enough economic benefits to justify their very large price tag. Beginning in the mid 1970s, nearly all OECD countries experienced a sustained decline both in public investment and in private sector output. Since infrastructure comprises the vast majority of public capital in these countries, this led many economists to conclude that underinvestment in infrastructure was largely responsible for the low growth rates in output and productivity which were experienced by these countries. In our paper, we discuss the findings in the literature with respect to both econometric and modeling deficiencies. Based on these criticisms, we develop a cost function modeling approach which includes public transport infrastructure capital, perform an econometric analysis and discuss several of our estimates of infrastructure productivity effects. The paper concludes that, in nearly all production sectors (except oil/agriculture), the public transport infrastructure investments made in Norway over the last 20 years significantly reduced private production costs and altered demand for private inputs. However, we find such effects to be statistically insignificant at the aggregate level.
Keywords: C32; E62; H54; R42; 330; Infrastructure; public transport investment; economic growth.